2010
DOI: 10.1103/physrevb.82.024524
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for time-reversal symmetry breaking in superconductingPrPt4Ge12

Abstract: Zero-and longitudinal-field muon-spin-rotation ͑SR͒ experiments were performed on the superconductors PrPt 4 Ge 12 and LaPt 4 Ge 12 . In PrPt 4 Ge 12 below T c a spontaneous magnetization with a temperature variation resembling that of the superfluid density appears. This observation implies time-reversal symmetry ͑TRS͒ breaking in PrPt 4 Ge 12 below T c = 7.9 K. This remarkably high T c for an anomalous superconductor and the weak and gradual change in T c and of the related specific-heat anomaly upon La subs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
111
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 38 publications
11
111
2
Order By: Relevance
“…If one of the two bands is related to the presence of spontaneous magnetization in PrPt 4 Ge 12 and vanishes with the substitution of La, it may explain the smooth variation in the spontaneous magnetization as a function of La concentration in Pr x La 1−x Pt 4 Ge 12 observed in μSR measurements. 9 This study has suggested one possible explanation based our experimental data; to confirm the multiband superconductivity in PrPt 4 Ge 12 , further experimental studies are necessary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If one of the two bands is related to the presence of spontaneous magnetization in PrPt 4 Ge 12 and vanishes with the substitution of La, it may explain the smooth variation in the spontaneous magnetization as a function of La concentration in Pr x La 1−x Pt 4 Ge 12 observed in μSR measurements. 9 This study has suggested one possible explanation based our experimental data; to confirm the multiband superconductivity in PrPt 4 Ge 12 , further experimental studies are necessary.…”
Section: Methodsmentioning
confidence: 99%
“…8 Previous comparative zero-and longitudinal-field μSR experiments on PrPt 4 Ge 12 and LaPt 4 Ge 12 reported spontaneous magnetization with a temperature variation resembling that of the superfluid density below T c only for PrPt 4 Ge 12 , implying time-reversal symmetry breaking in PrPt 4 Ge 12 . 9 While these studies have suggested unconventional superconductivity of PrPt 4 Ge 12 , very recent studies of the 73 Ge-nuclear quadrupole resonance (NQR) showed a coherence peak just below T c , indicating that the superconductivity is accounted for in terms of the conventional BCS regime. 10 In order to understand the anomalous superconducting properties of PrPt 4 Ge 12 , it is crucial to directly observe the superconducting gap.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a number of investigations including photoemission, magnetization, penetration depth, and specific heat revealed multiband superconductivity in this compound 13,[16][17][18][19] . The continuous evolution of T c across the doping series (Pr 1−x La x )Pt 4 Ge 12 suggests compatible order parameters of the end members PrPt 4 Ge 12 and LaPt 4 Ge 12 14 . However, the few existing investigations on LaPt 4 Ge 12 point towards a single isotropic gap: the specific-heat jump ∆C/γ n T c is only slightly above the BCS value suggesting a weaker coupling than in PrPt 4 Ge 12 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a coherence peak was revealed in the nuclear spin-lattice relaxation rate 1/T 1 just below T c for PrPt 4 Ge 12 , which is unexpectedly suppressed in LaPt 4 Ge 12 [17]. However, the weak variation of T c and of the specific heat jump at T c with the Pr-content x in La 1−x Pr x Pt 4 Ge 12 suggests that the order parameters of the two end members are compatible [12] In this Letter, we report a comprehensive study of the magnetic penetration depth λ(T, B) and superfluid density ρ s (T ) of LaPt 4 Ge 12 by using a µSR experiment and a TDO-based technique. The London penetration depth λ L (T ), measured by the TDO method, follows exponential-type behavior in the low-temperature limit, suggesting nodeless superconductivity for LaPt 4 Ge 12 .…”
mentioning
confidence: 95%
“…Resembling those of PrOs 4 Sb 12 , zero-field µSR experiments showed evidence of time-reversal symmetry (TRS) breaking in the superconducting state of PrPt 4 Ge 12 , but not for LaPt 4 Ge 12 [11][12][13]. However, more recent experiments suggested multi-gap SC for PrPt 4 Ge 12 [14][15][16].…”
mentioning
confidence: 99%